CONCEPT EDUCATION ATHIYAH AL-ABRASYI AND RELEVANCE THE ERA 4.0 CURRICULUM IN INDONESIA - Widya Wulandari; Huzdaeni Rahmawati; Taufik Hidayat; Abdul Manaf Harahap; Dewi Widyawati (Kuttab : Jurnal Ilmu Pendidikan Islam, 2023)
The educational concept of Athiyah al-Abrasyi whose work can be considered in the curriculum in Indonesia. What cannot be denied is that we have entered the 4.0 era, so that the influence of this development can be prevented through education. This study aims to describe Athiyah al-Abrasyi's educational theory concepts and their relevance to the education curriculum system which is always updating with the influence of scientific and technological developments. This study uses a literature study with a qualitative approach. The results of the study state that there is relevance between Athiyah al-Abrasyi's educational concept and the education curriculum system in Indonesia which is being pursued in facing the 4.0 era and producing students who are of high quality and globally competitive. The relevance of democratic education theory is to develop itself independently and reject models that limit students to develop according to their abilities. Meanwhile, the relevance of character/morals education aims to produce quality graduates with good morals and character in the future. Through the Pancasila student profile project program which is currently being implemented in the Merdeka curriculum.